2015
DOI: 10.1007/s10546-015-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Turbulence in Katabatic Flows Below and Above the Wind-Speed Maximum

Abstract: Measurements of small-scale turbulence made in the atmospheric boundary layer over complex terrain during the Mountain Terrain Atmospheric Modeling and Observations (MATERHORN) Program are used to describe the structure of turbulence in katabatic flows. Turbulent and mean meteorological data were continuously measured on four towers deployed along the east lower slope (2-4 • ) of Granite Mountain near Salt Lake City in Utah, USA. The multi-level (up to seven) observations made during a 30-day long MATER-HORN f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 76 publications
2
91
0
Order By: Relevance
“…Despite being essentially turbulent, katabatic flows or other flows with a low-level wind maximum do not match the standard ABL structure [185,190,191]. Therefore, the applicability of MOST or of local scaling approaches for katabatic flow has been called into question [192] and is a matter of on-going debate [191].…”
Section: The Stable Boundary Layer Over Slopesmentioning
confidence: 99%
“…Despite being essentially turbulent, katabatic flows or other flows with a low-level wind maximum do not match the standard ABL structure [185,190,191]. Therefore, the applicability of MOST or of local scaling approaches for katabatic flow has been called into question [192] and is a matter of on-going debate [191].…”
Section: The Stable Boundary Layer Over Slopesmentioning
confidence: 99%
“…One of the important aspects of this research is the turbulent exchange and turbulence structure close to the surface. A recent analysis of observational data by Oldroyd et al (2016b) has shown the important role of the along-slope heat flux in the buoyant generation or suppression of the turbulent kinetic energy (TKE), thus supplementing earlier work (e.g., Horst and Doran 1988;Denby 1999;Grachev et al 2016 The buoyancy term in the TKE budget contains the vertical component of the turbulent heat flux, and may simply be shown to describe the work done by or against the buoyancy force during vertical displacements of particles involved in turbulent motions. In a horizontally homogeneous atmospheric boundary layer (hereafter, the abbreviation ABL will be used, and it will also imply the horizontally homogeneous case), horizontal components of the turbulent heat flux play no role in this energy transformation process.…”
Section: Introductionmentioning
confidence: 86%
“…This schematic explanation may apply to different situations identified in slope flows, such as those discussed by, e.g., Horst and Doran (1988), Grachev et al (2016), Oldroyd et al (2016b). In a horizontal planar coordinate frame, the term containing θ 2 in Eq.…”
Section: Turbulent Heat Fluxmentioning
confidence: 97%
See 1 more Smart Citation
“…In that case, the formulation of the Obukhov length in Eq. (9) may have to be modified to include scalar fluxes tilted to the gravity vector (Horst et al, 1988;Grachev et al, 2015). We did not attempt to derive such a formulation in the present study.…”
Section: Bulk-aerodynamic Methodsmentioning
confidence: 99%